Edukasi dan Penerapan Terapi Kipas sebagai Pendekatan Alternatif untuk Mengurangi Spastisitas dan Meningkatkan Koordinasi pada Pasien Pasca-Stroke - Dewi, Ni Luh Putu Thrisna; Wati, Ni Made Nopita; Lisnawati, Ketut; Sanjiwani, Anak Agung Sri; Sudarma, I Nyoman (Jurnal Abdimas Kesehatan (JAK), 2025)
Stroke is one of the leading causes of long-term disability, requiring continuous rehabilitative interventions. This community service program aimed to provide education and training on fan therapy as a non-pharmacological approach to help reduce spasticity and improve coordination in stroke survivors. The activity was conducted at the Amaranee Foundation in Bali, involving stroke survivors as participants. Initial assessments showed that the majority of participants had high blood pressure (64%) and normal blood glucose levels (71%). Before the educational session, most participants had a low level of knowledge (89.2%), but after the fan therapy education and practical demonstration, there was a significant improvement, with 64.2% reaching a moderate level and 35.8% achieving a high level of knowledge. Fan therapy was chosen for its ease of implementation, absence of side effects, and potential for independent application. Participants demonstrated high enthusiasm throughout the program and were able to practice basic fan therapy techniques to reduce muscle stiffness and enhance motor coordination. This program contributed positively to community-based rehabilitation efforts, particularly for stroke survivors in need of simple yet effective approaches. Fan therapy education is considered relevant as a sustainable recovery intervention within community settings.